Аssessment of the antinociceptive efficacy of varieties of multimodal low-opioid general anesthesia during laparoscopic renal surgery - Ovsiienko, T.; Bondar, M.; Loskutov, O. (Ukrainian Journal of Nephrology and Dialysis, 2022)
The main premise for the emergence of the concept of low-opioid general anesthesia was the phenomenon of the formation of drug/opioid dependence in patients undergoing surgery under multicomponent anesthesia with high doses of narcotic analgesics (opioids). Opioids were used as the main analgesics and in the postoperative period. The above factors contributed to the development of opiate addiction in operated patients in the late postoperative period. The mass nature of this phenomenon has become one of the most urgent problems in modern anesthesiology. Our study aimed to evaluate the antinociceptive/antistress efficacy of 3 types of low-opioid multimodal general anesthesia in laparoscopic renal surgery. Methods. Eighty patients who had undergone laparoscopic renal surgery under 3 types of general anesthesia were included in this prospective cohort study. All patients were operated under general anesthesia with tracheal intubation. Induction: intravenous (IV) propofol 2 mg/kg, fentanyl 1.5-2 μg/kg, atracurium 0.6 mg/kg. Maintenance of anesthesia: sevoflurane (MAC - 1.44±0.25% by volume). In group 1 (control group n = 26), analgesia was provided with fentanyl 3,89±2.03 μg/kg/h. In group 2 (n = 25), multimodal low-opioid general anesthesia was performed with fentanyl 1.76±1.2 μg/kg/h and IV lidocaine 1.5 mg/kg/h and subanesthetic doses of ketamine. In group 3 (n = 29), multimodal anesthesia with low opioids was performed with fentanyl 2.38±1.01 μg/kg/h in combination with dexmedetomidine 0.7 μg/kg/h. The efficacy of antinociceptive protection was assessed by the dynamics of changes in stress hormone levels, hemodynamic parameters, and blood glucose concentration. Results. The mean total dose of fentanyl used throughout the anesthetic period was: 369,23±83,75 μg in group 1, 216,0±47,26 μg in group 2, and 272,41±58,14 μg in group 3 (p < 0.001). Mean cortisol levels were significantly different before and after surgery in groups 1 and 2: 371,0±161,61 nmol/l vs 562,72±226,87 nmol/l (p < 0.01) and 531,08±218,02 nmol/l vs 831,33±235,32 nmol/l (p < 0.01), respectively. In group 3, we did not detect any statistical difference: 393,51±134,69 nmol/l and 436,37±188,09 nmol/l, respectively (p > 0.05). The mean level of adrenocorticotropic hormone increased significantly after surgery in all studied groups: 111.86% in group 1 (p < 0.01), 122.02% (p < 0.01) in group 2 and 78.59% (p < 0.01) in group 3. Blood glucose levels in the postoperative (p/o) period did not exceed 6,16±1,67 mmol/l (p > 0.05) in all groups. Hemodynamic parameters and BIS, which were maintained within 44±6.4%, indicated the adequacy of anesthesia and analgesia in the study groups. In group 1, 8 of 26 patients required additional analgesia with opioids during the p/o period (pain intensity on the VAS scale exceeded 4 points). In group 2 and group 3, 4 patients each required opioid analgesia, 16% and 15.38%, respectively. The next day after surgery, all patients were mobilized (sitting in bed, walking). Markers of renal function were also within normal range in all patients. Conclusion. The use of low-opioid multimodal anesthesia with IV lidocaine or dexmedetomidine during laparoscopic renal surgery provides an adequate anesthetic/antinociceptive effect. The use of dexmedetomidine in multimodal general anesthesia provides the greatest antinociceptive protection and reduces the stress response to surgery.